Details of the mouldings of the jangha and vedibandha of the temple - Temples of India Project Team (Jio Institute, 2024)
West-facing elevation of the main Mandaleshwar Mahadev Temple is seen here. Details of the mouldings of the jangha (wall) and vedibandha (basal mouldings) of the temple. The intermediate and corner projections of the temple are slender and narrow, devoid of any sculptures. Only the central projection has a sculpture inside a niche.